Pancasila as a Paradigm Groundslas Phyloshopie - Elsa Yulia Fitriyani; Alifia Nabila; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
This article will discuss the ethical position and function of Pancasila as the philosophical basis. Whether it's in the context of national development, unity to the method of thinking. This kind of idea has actually been formed and sparked by Soekarno when it was formulated with Syahrir and Agus Salim. The philosophical method intended by Soekarno is that Pancasila must be seen as a tool to realize the noble goals and ideals of the Indonesian nation. So the implication of the application of this method is the realization of a just and prosperous society.